1 / 12

120 likes | 259 Views

Lesson 2-4. Tangent, Velocity and Rates of Change Revisited. Objectives. Identify the average and instantaneous rates of change. Vocabulary. Average rate of change – ∆y/∆x (the slope of the secant line between two points on the curve)

Download Presentation
## Lesson 2-4

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Lesson 2-4**Tangent, Velocity and Rates of Change Revisited**Objectives**• Identify the average and instantaneous rates of change**Vocabulary**• Average rate of change – ∆y/∆x (the slope of the secant line between two points on the curve) • Instantaneous rate of change – lim ∆y/∆x (∆x→0) (the slope of the tangent line at a point on the curve)**Average Rate of Change**Average Rate of Change – slope of the secant line Q f(a+h) P f(a) secant h = b - a a h b ∆y f(a+h) – f(a) ms = ----- = ----------------- ∆x h**Instantaneous Rate of Change**Instantaneous Rate of Change– slope of the tangent line (derivative of the function evaluated at the point) mt ms Q f(a+h) P As Q gets closer and closer to P, h (∆x) gets closer to 0; and the slope of the secant line, ms, approaches the slope of the tangent line, mt f(a) a h b ∆y f(a+h) – f(a) mt = lim ----- = lim ----------------- ∆x h h→0 ∆x→0**Average vs Instantaneous Rate of Change**Average Rate of Change – slope of the secant line Q f(a+h) ∆y f(a+h) – f(a) ms = ----- = ----------------- ∆x h P f(a) a h b Instantaneous Rate of Change – slope of the tangent line (derivative of the function evaluated at the point) mt Q As Q gets closer and closer to P, h (∆x) gets closer to 0; and the slope of the secant line, ms, approaches the slope of the tangent line, mt f(a+h) P f(a) ∆y f(a+h) – f(a) mt = lim ----- = lim ----------------- ∆x h h→0 ∆x→0 a h b**Example 1**Find the slope of the tangent line to the curve f(x) = 3 – 2x – 2x2 where x = 1. f(1+h) – f(1) lim --------------------- = h0 h f(a+h) – f(a) lim --------------------- = h0 h (-1 - 6h - 2h²) – (-1) lim --------------------------- = h0 h f(1) = 3 - 2 - 2 = -1 f(1+h) = 3 - 2(1+h) - 2(1+h)² = 3 - 2 - 2h - 2 - 4h -2h² = -1 - 6h - 2h² -6h -2h² lim ------------- = h0 h lim -6 – 2h = -6 h0**Example 2**Find the slope of the tangent line (using the definition) where f(x) = 1/(x-1) and a = 2. f(2+h) – f(2) lim --------------------- = h0 h f(a+h) – f(a) lim --------------------- = h0 h (1/(h+1)) – (1) lim --------------------- = h0 h f(2) = 1/(2-1) = 1 f(2+h) = 1/(2+h – 1) = 1/(h + 1) - h / (h + 1) lim ---------------- = h0 h 1 h + 1 - h ------ - --------- = ----------- h + 1 h + 1 h + 1 - 1 lim ---------- = - 1 h0 h + 1**Example 3**Find the instantaneous velocity at time t = 3 seconds if the particle’s position at time is given by f(t) = t2 + 2t ft. f(3+h) – f(3) lim --------------------- = h0 h f(a+h) – f(a) lim --------------------- = h0 h (h² + 8h + 15) – (15) lim --------------------------- = h0 h f(3) = 9 + 6 = 15 f(3+h) = (3+h)² + 2(3+h) = h² + 6h + 9 + 6 + 2h = h² + 8h + 15 h² + 8h lim ------------- = h0 h lim h + 8 = 8 h0**Example 4**For a particle whose position at time t is f(t) = 6t2 - 4t +1ft.: a. Find the average velocity over the following intervals: • [1, 4] • [1, 2] • [1, 1.2] • [1, 1.01] ∆y Ave vel = ms = --------- ∆x f(4) – f(1) 81 – 3 78 ---------------- = ------------- = -------- = 26 4 – 1 3 3 f(2) – f(1) 17 - 3 ---------------- = ------------ = 14 2 – 1 1 f(1.2) – f(1) 4.84 - 3 1.84 ------------------ = -------------- = -------------- = 9.2 1.2 – 1 0.2 0.2 f(1.01) – f(1) 3.0806 - 3 .0806 -------------------- = --------------- = ------------- = 8.06 1.01 – 1 .01 .01**Example 4 continued**For a particle whose position at time t is f(t) = 6t2 - 4t +1 ft.: b. Find the instantaneous velocity of the particle at t = 1 sec. f(1+h) – f(1) lim --------------------- = h0 h f(a+h) – f(a) lim --------------------- = h0 h (6h² + 8h + 3) – (3) lim --------------------------- = h0 h f(1) = 6 - 4 + 1 = 3 f(1+h) = 6(1+h)² - 4(1+h) + 1 = 6h² + 12h + 6 – 4h – 4 + 1 = 6h² + 8h + 3 6h² + 8h lim ------------- = h0 h lim 6h + 8 = 8 h0**Summary**• Summary: • Average rate of change is the slope of the secant line • Instantaneous rate of change is the slope of the tangent line • Limit of m secant = m tangent as ∆x →0

More Related